A general approach to developing debris penetration equations. Issue 1 (March 2023) - Wathugala, Gamage Wijesena "Wije"
Abstract : Over the years, various penetration equations were developed and used for engineering applications. They were generally developed based on semi-empirical methods. The basic assumptions used to derive some widely used equations for debris penetrating thin plates such as FAA-JTCG penetration equation are not known and therefore, confusions exist on selecting the correct input parameters. Extending these equations to new projectile shapes and materials is also difficult since the consequences of some of the assumptions are unknown. In this paper, we present a general procedure to develop theoretically sound, fast, analytical solutions to the penetration and perforation process. A general approach to deriving penetration equations for any kinetically admissible penetration mechanism is presented and illustrated with three examples: (1) plugging mechanism, (2) petaling mechanism, and (3) mixed mechanism with petaling and shearing. Penetration equations derived were reformatted with non-dimensional parameters. Shape factors were identified/defined that can capture the effects of projectile shape and orientation, and the shape of the plug. They were computed for common projectile shapes and orientations. The shape factors for three cardinal orientations of a cube can be used to quantify the effect of potential random orientations of falling debris impacting and perforating fast moving aircraft, injuring passengers, and crew. Non-dimensional terms in these penetration equations help to improve understanding of the penetration process. The proposed method can also be used to extend penetration equations to composite targets.